2021
DOI: 10.1080/15402002.2021.1890597
|View full text |Cite
|
Sign up to set email alerts
|

Early Impact of the COVID-19 Outbreak on Sleep in a Large Spanish Sample

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) forced Spain to implement unprecedented lockdown restriction. In this context, different factors could worsen sleep quality, but the impact of the pandemic and lockdown on sleep is still mostly unknown. In this cross-sectional study, we describe self-reported sleep disturbances in people without mental health disorders from a large Spanish sample (n = 15,070). Methods: During the early phase of the lockdown (19-26 March), an online survey was launched using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The most noticeable changes were found in environmental exposures, physical activity and restorative sleep that seem to be the lifestyle behaviors most sensitive to the effects of strict lockdown and mandatory home isolation issued during the early phase of the pandemic. Several studies across the world have also observed the remarkable effects of confinement on these three behaviors ( Colley et al., 2020 ; Dal Santo et al., 2021 ; Qin et al., 2020 ; Rolland et al, 2020 ; Smith et al., 2020 ; Wiederhold et al., 2020 ). Moreover, a longitudinal study found a trend towards the disappearance of the sleep disturbances after the lockdown release in France ( Beck et al., 2021 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The most noticeable changes were found in environmental exposures, physical activity and restorative sleep that seem to be the lifestyle behaviors most sensitive to the effects of strict lockdown and mandatory home isolation issued during the early phase of the pandemic. Several studies across the world have also observed the remarkable effects of confinement on these three behaviors ( Colley et al., 2020 ; Dal Santo et al., 2021 ; Qin et al., 2020 ; Rolland et al, 2020 ; Smith et al., 2020 ; Wiederhold et al., 2020 ). Moreover, a longitudinal study found a trend towards the disappearance of the sleep disturbances after the lockdown release in France ( Beck et al., 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…Growing evidence supports that COVID-19 pandemic has a significant impact on most lifestyle behaviors, especially during populations lockdowns ( Branchi and Giulani, 2021 ; Verdolini et al., 2021 ). For instance, research across the world estimates the prevalence of sleep disturbances between 21.9 and 55.8% ( Cellini et al., 2020 ; Dal Santo et al., 2021 ; Ernstsen and Havnen, 2020 ; Fu et al., 2020 ; Li et al., 2020 ) which in turn were significantly associated with anxiety and depressive symptoms ( Cellini et al., 2020 ; Ernstsen and Havnen, 2020 ; Fu et al., 2020 ; Li et al., 2020 ; Smith et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…While most studies among the general population, by their very nature, include individuals in lockdown (which was essentially the norm in most countries around the world during the pandemic), some researchers have attempted to study the effects of lockdown and/or quarantine periods in particular on sleep dysfunction. A large Spanish study [ 20 ] conducted in over 15,000 subjects in the early phase of the lockdown showed high rates of difficulty initiating or maintaining sleep (23.9%), associated with higher age, female sex, reduction in income, having elderly dependents, alcohol use, depression, anxiety and stress; conversely, indulging in hobbies such as painting or listening to music were protective factors. A web-based study among 1,908 individuals in lockdown in six different countries (Greece, Switzerland, Austria, Germany, France, and Brazil) showed that sleep duration increased by a small amount (0.31 hours); 15% of participants characterized their sleep as bad and 37.9% as average during the lockdown week, and a third of individuals reported worse quality of sleep during the lockdown week than under normal conditions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the presence of COVID-19 related nightmares has been associated with symptoms of generalized anxiety disorder in healthcare providers in Colombia (Monterrosa-Castro, Redondo-Mendoza, & Mercado-Lara, 2020). Similarly, the presence of COVID-19 related dreams in a large Spanish sample was associated with many factors, including having infected family or friends, reading news about coronavirus, and having higher depression, anxiety or stress scores (Dal Santo et al, 2021). With regards to specific features of dream content, Brazilian (Mota et al, 2020), U.S. (Barrett, 2020), Italian (Gorgoni et al, 2021;Iorio, Sommantico, & Parrello, 2020;Scarpelli et al, 2021), Canadian (Kilius et al, 2021) and Chinese (Wang, Zemmelman, Hong, Feng, & Shen, 2020) teams, all reported increases in negative dreams during the pandemic, including increase in themes of anxiety, sadness, aggressive interactions and preoccupations with health.…”
Section: Dreams During Covid-19mentioning
confidence: 92%
“…Lastly, in addition to the well-established notion that dysphoric dreaming reacts to stressors and is affected by psychopathology, an emerging body of research suggests that bad dreams and nightmares may exacerbate or even trigger increased stress response (Garcia et al, 2021), contribute to daytime distress (Gehrman, Harb, Cook, Barilla, & Ross, 2015;Gieselmann et al, 2020;Levin & Fireman, 2002) and symptoms of psychopathology, including anxiety (Roberts, Lennings, & Heard, 2009) and depression (Hedstrom et al, 2021). Thus, to account for the possibility of the bi-directional relationship between dreams, stress and psychopathology, we tested whether dream, bad dream and nightmare frequency, and the most frequent dream topics predicted levels of stress and symptoms of depression and anxiety.…”
Section: Dreams Nightmares Stress and Symptoms Of Depression And Anxietymentioning
confidence: 99%